2003
DOI: 10.3386/w9953
|View full text |Cite
|
Sign up to set email alerts
|

The Draw of Home: How Teachers' Preferences for Proximity Disadvantage Urban Schools

Abstract: This paper explores a little understood aspect of labor markets, their spatial geography. Using data from New York State, we find teacher labor markets to be geographically very small. Teachers express preferences to teach close to where they grew up and, controlling for proximity, they prefer areas with characteristics similar to their hometown. We discuss implications of these preferences for the successful recruitment of teachers, including the potential benefits of local recruiting and training. We also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
289
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(312 citation statements)
references
References 4 publications
21
289
0
2
Order By: Relevance
“…Individual characteristics, including demographic factors like age, race, socioeconomic status, marital status, geography, and number of children as well as the personal factors of education level, academic ability, and individual characteristics, have been shown to matter for teacher retention (Boe, Bobbitt, Cook, Whitener, & Weber, 1997;Boyd, Lankford, Loeb, & Wyckoff, 2005;Dworkin, 1980;Heyns, 1988;Vance & Schlechty, 1982). Likewise, contextual characteristics like salary; school factors including facilities, size, support, leadership, and culture; the population; discipline; and motivation of the student body also make a difference for teachers' career plans (Bobbitt, Faupel, & Burns, 1991;Bridge, Cunningham, & Forsbach, 1978;Buckley, Schneider, & Shang, 2005;Haberman & Rickards, 1990;Murnane & Olsen, 1990;Theobald, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Individual characteristics, including demographic factors like age, race, socioeconomic status, marital status, geography, and number of children as well as the personal factors of education level, academic ability, and individual characteristics, have been shown to matter for teacher retention (Boe, Bobbitt, Cook, Whitener, & Weber, 1997;Boyd, Lankford, Loeb, & Wyckoff, 2005;Dworkin, 1980;Heyns, 1988;Vance & Schlechty, 1982). Likewise, contextual characteristics like salary; school factors including facilities, size, support, leadership, and culture; the population; discipline; and motivation of the student body also make a difference for teachers' career plans (Bobbitt, Faupel, & Burns, 1991;Bridge, Cunningham, & Forsbach, 1978;Buckley, Schneider, & Shang, 2005;Haberman & Rickards, 1990;Murnane & Olsen, 1990;Theobald, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that those entering teaching tend to prefer to teach in schools like those they themselves attended and, hence, seek teaching jobs close to home (e.g., Boyd et al, 2005;Loeb & Reininger, 2004 (Barnes, 2006). In short, the degree to which the teacher labor market is local, regional, or national varies.…”
Section: Local and National Labor Marketsmentioning
confidence: 99%
“…En effet, certaines études avancent que les écoles comprenant une grande proportion d'élèves de faibles niveaux scolaire et socioéconomique sont plus en proie au décrochage (Boyd et al 2005;Haycock 2000;Loeb et al 2005). Le placement des nouveaux enseignants paraît d'autant plus important que ces derniers se sentent généralement isolés lors de leur insertion professionnelle (Gonzales 1995;Schlagal et al 1996).…”
Section: Facteurs De Décrochage Liés à L'environnement Socialunclassified